Incorporating robotic surgery into the management of ovarian cancer after neoadjuvant chemotherapy. Issue 9 (9th October 2019) - Abitbol, Jeremie; Gotlieb, Walter; Zeng, Ziggy; Ramanakumar, Agnihotram; Kessous, Roy; Kogan, Liron; Pare-Miron, Valerie; Rombaldi, Marcelo; Salvador, Shannon; Kucukyazici, Beste; Brin, Sonya; How, Jeffrey; et al.
Abstract : Introduction: With the rapid uptake of robotic surgery in surgical oncology, its use in the treatment of epithelial ovarian cancers is being evaluated. Complete cytoreduction represents the goal of surgery either at primary cytoreduction or after neoadjuvant chemotherapy in the setting of interval cytoreduction. In selected patients, the extent of disease would enable minimally invasive surgery. The objective of this study was to evaluate the impact of introducing robotic surgery for interval cytoreduction of selected patients with stage III–IV ovarian cancer. Methods: All patients who underwent surgery from November 2008 to 2014 (concurrent time period when robotic and open surgery were used simultaneously) after receiving neoadjuvant chemotherapy for advanced ovarian cancer (stage III–IV) were compared with all consecutive patients who underwent cytoreductive surgery by laparotomy after neoadjuvant chemotherapy between January 2006 and November 2008. Inclusion criteria included an interval cytoreductive surgery by laparotomy or robotic assistance for stage III–IV non-mucinous epithelial ovarian, fallopian tube, or primary peritoneal cancer. Exclusion criteria included patients treated concurrently for a non-gynecologic cancer, as well as secondary cytoreductive surgeries and diagnostic surgeries without an attempt at tumor reduction. Overall survival, progression-free survival, and peri-operative outcomes were compared for the entire patient cohort with those with advanced ovarian cancer who received neoadjuvant chemotherapy immediately before and after the introduction of robotic surgery. Results: A total of 91 patients were selected to undergo interval cytoreduction either via robotic surgery (n=57) or laparotomy (n=34) after the administration of neoadjuvant chemotherapy. The median age of the cohort was 65 years (range 24–88), 78% had stage III disease, and the median follow-up time was 37 months (5.6–91.4 months). The median survival was 42.8±3.1 months in the period where both robotic surgery and laparotomy were offered compared with 37.9±9.8 months in the time period preceding when only laparotomy was performed (p=0.6). All patients selected to undergo interval robotic cytoreduction following neoadjuvant chemotherapy had a reduction of cancer antigen 125 by at least 80%, resolution of ascites, and CT findings suggesting the potential to achieve optimal interval cytoreduction. All these patients achieved optimal cytoreduction with <1 cm residual disease, including 82% with no residual disease. The median blood loss was 100 mL (mean 135 mL, range 10–1250 mL), and the median hospital stay was 1 day. Conclusion: Robotic interval cytoreductive surgery is feasible in well-selected patients. Future studies should aim to define ideal patients for minimally invasive cytoreductive surgery.